The enhanced biological methanation performance in trickle-bed reactor by different continuous hydrogen supply from nano-zero valent iron corrosion. (December 2022) - Li, Yong; Zhang, Zhou; Tang, Jieyu; Zhao, Mingxing; Huang, Zhenxing; Shi, Wansheng; Ruan, Wenquan
Abstract: In this paper, the hydrogen (H2 ) supply to trickle-bed reactor (TBR) in endogenous and exogenous ways by nano-zero-valent iron (nZVI) corrosion was indicated, in order to increase the biogas generation and methane (CH4 ) content from wastewater. The results showed that the nZVI corrosion H2 supply method increased the biogas generation in TBR. The daily average CH4 yields of TBR in stages 1–4 increased by 23.99 %, 35.76 %, 49.40 % and 56.13 % compared with control stage, respectively, and the highest CH4 content of 90.72 % was achieved in stage 3. The changes of enzyme concentration indicated that iron from nZVI enhanced the activities of acetate kinase and dehydrogenase, however, the activity of coenzyme F420 was lower due to the presence of homoacetogenic acetate formation that enhanced the acetoclastic methanogenesis pathway. Changes in the structure of the microbial community played an important role in the mechanism of CH4 enhancement, and the analysis of microbial abundance showed that the additions of nZVI and ferrous iron (Fe 2+ ) changed the microbial communities, with increased abundances of hydrogenotrophic methanogens and homoacetogen. Graphical abstract: Unlabelled Image Highlights: The performance of TBR under four H2 supply ways from nZVI corrosion was investigated. The average daily biogas and CH4 yield increased by 39.72 mL biogas/gCOD and 56.13 % after nZVI addition, respectively. The acetate kinase, dehydrogenase and F420 activity in TBR were affected by nZVI addition. The abundance of hydrogenotrophic methanogens and homoacetogen was increased after H2 supply.